The cultivation of root and tuber crops in the Caribbean countries: Report on the 1985 workshop of the Caribbean collaborative agricultural research network - Ferguson, T.U. (International Center for Tropical Agriculture, 1986)
In July 1985 representatives from 16 countries and institutions of the Caribbean region met in Guadeloupe to define common regional problems for the further development of root crops (including cassava) in the area, evaluate the potential for development of these crops, and develop a program for regional network activities including research, exchange, training, and technology transfer. (CIAT)